Case Report: Liver as a Source of Hematopoietic Stem Cells After Liver Transplantation Following Hematopoietic Stem Cell Transplantation - Tomasz Jarmoliński; Monika Rosa; Blanka Rybka; Renata Ryczan-Krawczyk; Kornelia Gajek; Katarzyna Bogunia-Kubik; Maja Klaudel-Dreszler; Piotr Czubkowski; Piotr Kaliciński; Joanna Teisseyre; Marek Stefanowicz; Ewa Gorczyńska; et al. (Frontiers Media S.A., 2022)
We report a child with Fanconi anemia who, after hematopoietic stem cell transplantation (HSCT) complicated by acute graft-versus-host disease (GVHD), underwent orthotopic liver transplantation (OLT). Approximately 1 month after OLT, the presence of third-party genetic material from the liver donor was noted and in the next few weeks, the chimerism assessment revealed 100% liver donor leukocytes in the peripheral blood. The rapidly progressing GVHD with gut involvement resulted in patient's death 6 months after OLT. The liver can act as a clinically significant source of hematopoietic stem cells, and the liver donor's young age must be emphasized as potentially predisposing to this phenomenon. Transfer of OLT hematopoietic stem cells may not have clinical significance unless the patient is not immunocompetent or develops liver-transplantation associated GVHD, that can result in lymphocyte mediated elimination of original hematopoiesis. Patients with preexisting immunity disorder (such as primary or secondary immunodeficiency) might require intensified immunosuppressive therapy in peritransplant period as a prevention of liver-transplantation associated GVHD. Close monitoring of hematopoietic chimerism after OLT is warranted in patients at risk, because cytopenia or OLT hematopoiesis can reflect subclinical GVHD and further studies are necessary to elucidate this phenomenon.